Catatonia in dementia managed with electroconvulsive therapy: A case report and review of the evidence - Sandeep Grover; Swapnajeet Sahoo; C Pradeep; B Srinivas; Parampreet Singh (Journal of Geriatric Mental Health, 2017)
There is limited literature on catatonia as a presenting manifestation of dementia. Further, whenever catatonia occurs in patients with dementia, it often responds to lorazepam. There is limited literature on use of electroconvulsive therapy for management of catatonia among patients with dementia. In this report, we present a case of catatonia occurring during dementia of Lewy body which did not respond to lorazepam but responded to use of electroconvulsive therapy.